2007
DOI: 10.3168/jds.2006-573
|View full text |Cite
|
Sign up to set email alerts
|

Production Performance and Milk Composition of Dairy Cows Fed Whole or Ground Flaxseed With or Without Monensin

Abstract: Eight multiparous Holstein cows averaging 570 +/- 43 kg of body weight and 60 +/- 20 d in milk were used in a double Latin square design with four 21-d experimental periods to determine the effects of feeding ground or whole flaxseed with or without monensin supplementation (0.02% on a dry matter basis) on milk production and composition, feed intake, digestion, blood composition, and fatty acid profile of milk. Intake of dry matter was similar among treatments. Cows fed whole flaxseed had higher digestibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
29
3
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 40 publications
14
29
3
4
Order By: Relevance
“…Replacement The average concentration of N-urea in milk (N/dL) in the present experiment was 18.91 mg of N/dL, which was higher than that obtained by Broderick and Clayton (1997), who reported an average value of 14.8 mg of N/dL, ranging from 3 to 28 mg of N/dL, but close to those obtanied by Da Silva et al (2007), i.e. 17 to 18.5 mg of N/dL.…”
Section: Resultscontrasting
confidence: 49%
“…Replacement The average concentration of N-urea in milk (N/dL) in the present experiment was 18.91 mg of N/dL, which was higher than that obtained by Broderick and Clayton (1997), who reported an average value of 14.8 mg of N/dL, ranging from 3 to 28 mg of N/dL, but close to those obtanied by Da Silva et al (2007), i.e. 17 to 18.5 mg of N/dL.…”
Section: Resultscontrasting
confidence: 49%
“…Micronizing flaxseed reduced protein degradability of flaxseed in the rumen (Mustafa et al, 2002;Gonthier et al, 2004), but failed to increase milk ALA concentration compared to cows fed ground raw flaxseed (Gonthier et al, 2005). However, da Silva et al (2007) showed that cows fed ground flaxseed increased ALA concentration in milk compared with those fed whole flaxseed. Furthermore, Maddock et al (2006) reported that yearling beef heifers fed processed flaxseed (either by rolling or grinding) increased ALA concentration in longissium lumborum phospholipids or neutral lipids compared with those fed whole flaxseed.…”
Section: Resultsmentioning
confidence: 76%
“…These discrepancies might be due to the differences in passage rate of ALA or extent of microbial biohydrogenation in the rumen. The apparent total tract EE digestibility for cows fed whole flaxseed was 734 g kg − 1 for the study of da Silva et al (2007), whereas it was 486 g kg − 1 for the present study. The ALA in whole flaxseed treatment for the previous study might have been biohydrogenated in the rumen to a greater extent compared with that for the present study, reducing the absorption of ALA in the small intestine.…”
Section: Resultsmentioning
confidence: 86%
“…Moreover, a combination of ground flaxseed and monensin resulted in higher milk fat concentration of trans11-18:1 than when feeding ground flaxseed without monensin or whole flaxseed with or without monensin (Da Silva et al, 2007). A greater oil release with ground rather than whole seed may explain the higher trans11-18:1 proportion in milk fat observed in the experiment of Da Silva et al (2007), thus suggesting that free oil may lead to similar trans11-18:1 proportion increases when supplemented with monensin. Indeed, monensin interacts with soybean oil to linearly increase concentration of total trans11-18:1 in milk fat (Alzahal et al, 2008).…”
Section: Introductionmentioning
confidence: 98%